In vitro gastroduodenal and jejunal brush border membrane digestion of raw and roasted tree nuts. (October 2020) - Di Stasio, Luigia; d'Acierno, Antonio; Picariello, Gianluca; Ferranti, Pasquale; Nitride, Chiara; Mamone, Gianfranco
Graphical abstract: Highlights: Roasting affects differently the digestion stability of tree nut allergens. Brush border enzymes enhance the release of known epitopes of roasted almonds. Epitopes of roasted walnuts and hazelnuts were mostly degraded by brush border enzymes. Abstract: Heat treatments induce chemical/physical modifications, which may affect the stability to enzymatic digestion and consequently the allergenicity of food proteins to a varying extent, depending on the time/temperature regimen. Herein, we evaluated the stability to digestion of whole tree nut (walnuts, hazelnuts and almonds) allergens in a food digestion model reflecting the real one by, taking into consideration the allergen-containing processed (roasted) food. To this aim, whole raw and roasted tree nuts were subjected to in vitro digestion combining the harmonized oral-gastric-duodenal digestion models with brush border membrane enzymes (BBM) to simulate the jejunal degradation of peptides. The degradation of allergens was monitored by integrated proteomic/peptidomic and bio-informatic tools. Roasting increased digestibility of tree nuts, since very few peptides were detected in digested samples (<6.5 kDa fraction). After BBM digestion step, the degradation of peptides was enhanced in roasted walnuts and hazelnuts compared to the raw counterpart. Conversely, almond allergens showed a different behaviour, since the presence of resistant peptides was more evident for roasted almonds, probably because of the hydrolysis of high molecular weight aggregates generated during roasting. Our results provide new insight into the relationship between thermal processing and metabolic fate of tree nut allergens, highlighting the importance of investigating the digestion stability of whole allergenic food, rather than purified proteins.